"Graeca non leguntur" : Zu den Ursprüngen des europäischen Rechts im antiken Griechenland Das griechische Recht in seinem kulturhistorischen Umfeld: Beispiele aus Dichtung, Geschichtsschreibung, Philosophie und Kautelarjuris. (Harrassowitz Verlag, 2014)
The emergence of culture can be studied in the Greeks as the interaction of the creative forces of a society: This is how the Greeks became the inventors of 'politics' and other social disciplines. Philosophers were interested in law, poetry, history, mathematics and zoology beyond their own discipline. Citizens went to the theater, enjoyed works of art on the agora and in sanctuaries or attended Herodotus' history lectures. The same applied to participation in public life, which for the first time could be experienced directly - in the people's assembly (Ekklesia), the people's court (Heliaia), in the council (Boulé) or at the numerous festivals. This resulted in scientifically lived interdisciplinarity: Aristotle taught 'Rhetoric' at Plato's Academy when he was young, wrote a 'Poetics' and later a 'Politics' at the same time, was interested in law, the constitution and Solon's legislation and also wrote philosophical works. In addition, the great thinkers by no means kept to themselves, but endeavored to make their knowledge accessible to other people in the theater, in lectures or funeral orations: culture served the community. Volume III of Heinz Barta's Graeca project on the importance of ancient Greek legal development deals with the relationships between poetry and historiography, law and justice and the already highly developed Greek legal practice, which was of great importance as cautarian jurisprudence, from which Rome and Europe in turn benefited . – Legislation, cauteary jurisprudence, rhetoric and the legal thinking of philosophers led to the emergence of Greek jurisprudence.